GAMBARAN PERILAKU PENGGUNAAN ALAT PELINDUNG DIRI DOKTER GIGI MUDA PADA TINDAKAN PENCABUTAN GIGI DI RSGM UNIMUS - Nur Khamilatusy Sholekhah; Briliana Ikrimazahra (Indonesian Journal of Dentistry, 2023)
Background: Health workers have a risk of exposure to infection. One of the actions in the field of dentistry with a high risk of contracting infection is tooth extraction. Transmission of infection can occur from the decreased behavior of dentists towards personal protective equipment because many medical personnel ignore personal protective equipment. The purpose of this study was to describe the behavior of young dentists using PPE during tooth extraction at the RSGM Unimus.Method: This research uses quantitative research with descriptive observational research design. The number of respondents was 60 young dentists at RSGM Unimus. Collecting data by providing a questionnaire about the prevention and control of cross-infection carried out on tooth extraction in the form of the use of PPE (Personal Protective Equipment) through the google form. The scores for each question on the Guttman scale are added up and then a percentage is made. good category 76-100%, sufficient category 60-75%, and less category 60%.Result: The use of Personal Protective Equipment (PPE) was found that the majority of respondents were in the good category as many as 58 people (96.7%), and the less category as many as 1 person (1.7%), and those who were included in the sufficient category were 1 person (1.7%).Conclusion: The behavior of using personal protective equipment for young dentists during tooth extraction at the Unimus Hospital was good in wearing masks (100%), protective gowns (100%), google/protective glasses (95%), protective shoes (95%) and head protection (96.7%).